Phytochemical characteristics, antimitotic, cytotoxic and antitumor activities of bark extract of Streblus asper Lour - Alamgir, ANM; Rahman, Minhajur; Rahman, Ataur (Bangladesh Journal of Botany, 2013)
Ethanol extract of the stem bark of Streblus asper Lour was considered for qualitative assessment for its secondary metabolites content like alkaloids, glycosides, sterols and others. Bark extract revealed anticarcenogenic i.e. antimitotic, cytotoxic and antitumor activities. Results of different anticarcenogenic activities of the bark extract were discussed in relation to its secondary metabolite contents. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15801 Bangladesh J. Bot. 42(1): 17-22, 2013 (June)